2021
DOI: 10.1177/0300060520986668
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of fetal right ventricular diverticulum with massive pericardial effusion in one of monochorionic diamniotic twins: a case report with a favorable outcome following in utero pericardiocentesis

Abstract: Background Congenital ventricular diverticulum is a rare abnormality that may occur as an isolated malformation. Most cases are accompanied by pericardial effusion. Prenatal counseling can be difficult because the prognosis is uncertain and there is no consensus approach to prenatal management. Case presentation: We describe a case of congenital cardiac diverticulum complicated by large pericardial effusion in one of monochorionic diamniotic twins. The case was diagnosed by ultrasonography at 21 weeks of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…TrueVue Glass has an obvious advantage in the diagnosis of pulmonary artery sling, and it is the first time that an innovative 3D ultrasound technology has been used to diagnose such rare cardiovascular malformations. Rare ventricular diverticulum, with its narrow entrance and long shape, may be easily missed or misdiagnosed as a paracardiac vessel on 2D ultrasound ( Sozzi et al, 2017 ; Wang et al, 2021 ). The TrueVue Light highlights the interior space features of the diverticulum.…”
Section: Discussionmentioning
confidence: 99%
“…TrueVue Glass has an obvious advantage in the diagnosis of pulmonary artery sling, and it is the first time that an innovative 3D ultrasound technology has been used to diagnose such rare cardiovascular malformations. Rare ventricular diverticulum, with its narrow entrance and long shape, may be easily missed or misdiagnosed as a paracardiac vessel on 2D ultrasound ( Sozzi et al, 2017 ; Wang et al, 2021 ). The TrueVue Light highlights the interior space features of the diverticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular diverticulum is a rare cardiac malformation, and one report estimated its approximate incidence to be 0.013% [ 6 ]. Although one case of RV diverticulum was reported at a GA of 12 weeks, most cases (75%) were diagnosed after the first trimester [ 2 ]. According to a recent study, among the 40 reported cases, only two cases of CVD occurred in multiple pregnancies, which were monochorionic diamniotic twins [ 2 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital ventricular diverticulum (CVD) is a cardiac malformation defined as an outpouching lesion of a ventricle with normal contractility and thickness, and the advancement of prenatal sonography has led to its prenatal diagnosis [ 1 , 2 ]. In the prenatal period, CVD is reported in association with pericardial effusion, arrhythmia, and fetal hydrops or as an isolated condition [ 2 , 3 , 4 , 5 ]. When a ventricle shows outpouching, it is necessary to differentiate CVD from congenital ventricular aneurysm (CVA).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations